Development of a Speed ​​Training Model in Futsal Games - Pratama, Yudha Aqil; Fikri, Aprizal; Hardiyono, Bayu; Muslimin, Muslimin; Hidayat, Arif; Riyoko, Endie; Masrur, Muhammad (Universitas PGRI Palembang, 2024)
Speed ​​training is to improve a person's ability to move or complete tasks faster or move quickly from one place to another. This speed training is also often referred to as speed training with the aim of training speed in all fields of sport. The purpose of this study is to produce a speed training model in futsal games. The method used in this study is the ADDIE analysis, design, development implementation, evaluation method. The results of this study were obtained from expert validation that had been carried out involving three experts including 1 futsal coach, 1 futsal academic, 1 futsal practitioner. The instrument in this study used a questionnaire based on the results of the CVI and CVR analysis which obtained 0.5 or valid. It can be interpreted that the YAP 1 model is feasible to be used and applied to the speed training of extracurricular students in the city of Palembang